ANALISIS KEUNTUNGAN DAN TITIK IMPAS TERNAK AYAM KAMPUNG SUPER DAN AYAM BROILER DI DESA BANGUN HARJO BUAY MADANG TIMUR OKU TIMUR - Imam Sulaiman (Jurnal Bakti Agribisnis, 2017)
The objectives of this research are to: (1) To analyze the cost, income and income of chicken and chicken cattle in Bangu Harjo Village, Buay Madang Timur District, OKU Timur Regency, (2) To analyze whether broiler and joper cattle cultivated in Bangun Harjo Village, Buay Madang Timur Sub-district, OKU Timur Regency is beneficial, (3) To analyze break even point of broiler and joper livestock business in Bangun Harjo Village, Buay Madang Timur District, OKU Timur Regency. This research has been conducted in Bangun Harjo Village, Buay Madang Timur District, East OKU Regency. Site selection is done purposively with the consideration that in the village is able to represent from the existing population and have the criteria of research plan. Bangun Harjo village is a village whose majority population live as farmers and there are some farmers who seek the cultivation of super chicken (joper) and broiler (broiler). The study was conducted in June 2015. The study found that the total production cost incurred in the poultry livestock business in Bangun Harjo Village in one production process amounted to Rp 13,963,744, the average revenue was Rp 22,920,000 so that income Received amounted to Rp 8,956,256. The value of R / C ratio is 1.64 indicating that the chicken livestock business is profitable. The total production cost incurred in the broiler business in Bangun Harjo Village in one production process is Rp 30,609,006, the average revenue is Rp 54,676,250, so the income received is Rp 24,067,224. The value of R / C ratio is 1.79 indicates that the business of broiler livestock is profitable and BEP value of livestock production volume of chicken joper is 349 head, while the value of BEP price is Rp 24.569 / Tail and BEP value of broiler chicken production volume is equal to 2.017 Kg, while the BEP value of the price is Rp 8,496 / Kg which shows that the business of chicken and broiler cattle in Bangun Harjo Village is feasible financially.